Prognostic Significance Of Left Ventricular Diastolic Dysfunction With Preserved Systolic Function Following Acute Myocardial Infarction - Hussain, Mutaz F. (Journal of the Faculty of Medicine Baghdad, 2006)
Background : The contribution of diastolic dysfunction in patients with preserved left ventricular (LV) systolic function to impaired functional status and cardiac mortality in myocardial infarction (MI) is unknown. Materials and Methods : Assessment of LV diastolic function was performed by Doppler analysis of the mitral and pulmonary venous flow and the propagation velocity of early mitral flow by color M-mode Doppler echocardiography in 150 consecutive patients at day 5-7 following their first acute MI.Results : Patients were classified into four groups: group A: preserved LV systolic and diastolic function (n=59); group B: LV systolic dysfunction with preserved diastolic function (n=8); group C: LV diastolic dysfunction with preserved systolic function (n=49); group D: combined LV systolic and diastolic dysfunction (n=33). The cardiac mortality rate at 6 months was significantly higher in groups C (12%) and D (36%) compared to A (2.5%) (p